Determining the spatial variations of evapotranspiration rates in a semiarid region - Sorour, Wendy (University of the Witwatersrand, Johannesburg, 2024)
Evapotranspiration (ET) is one of the biggest ways in which water is transferred from water resources into the atmosphere as water vapor and understanding its variations is important for water resource management. This study determined land use land cover (LULC)-based ET and the influence of climatic events in Western Cape. Landsat 8, Surface Energy Balance System, Support Vector Machine, humidity, wind speed, surface pressure, temperature, and sunshine hours were used, during El Nino in 2015-2016, normal year in 2019-2020, and La Nina in 2020-2021. Median ET was calculated for each LULC type to determine their effect on ET. Climatic events increased ET compared to the normal year and increasing temperatures and rainfall during EL Nino and La Nina years respectively were the main drivers. Water had the lowest ET, and agricultural land had the highest. The results of this study can be used to create better water resource management plans
A research report submitted, in partial fulfillment of the requirements for the degree of Master of Science in Geographical Information Systems and Remote Sensing, to the School of Geography, Archaeology & Environmental Studies, in the Faculty of Science at the University of the Witwatersrand, Johannesburg, South Africa, 2024
Keywords: Climatic events; El Nino; Evapotranspiration; La Nina; LULC; SEBS; Western Cape; UCTD; SDG-13: Climate action